FXYD5: Na+/K+-ATPase Regulator in Health and Disease - Lubarski Gotliv, Irina (Frontiers in Cell and Developmental Biology, 2016)
FXYD5 (Dysadherin, RIC) is a single span type I membrane protein that plays multiple roles in regulation of cellular functions. It is expressed in a variety of epithelial tissues and acts as an auxiliary subunit of the Na+/ K+-ATPase. During the past decade, a correlation between enhanced expression of FXYD5 and tumor progression has been established for various tumor types. In this review, current knowledge on FXYD5 is discussed, including experimental data on the functional effects of FXYD5 on the Na+/ K+-ATPase. FXYD5 modulates cellular junctions, influences chemokine production, and affects cell adhesion. The accumulated data may provide a basis for understanding the molecular mechanisms underlying FXYD5 mediated phenotypes.